Spatiotemporal Variability and Change of the South China Spring Precipitation during 1961–2012 - Hong-Lan Liu; Qiang Zhang; Jun-Qin Guo; Jun-Guo Zhang; Sheng Wang (Advances in Meteorology)
We analyze precipitation data from 47 meteorological stations spanning between 1961 and 2012 and NCEP/NCAR reanalysis to understand spatiotemporal variability and change of spring precipitation of South China and their relations to atmospheric circulations. Empirical orthogonal function (EOF) analysis and rotated EOF (REOF) are used to reveal dominant spatial structures of precipitation anomaly and Mann-Kendall testing method to determine the temporal locations of abrupt changes during the analyzed time span. We find that the first spatial mode of the spring precipitation of the South China has a domain uniform structure; the second is dominated by a spatial dipole; and the third contains six variability centers. 1980s was the decade of the largest amount of precipitation while 1960s the decade of the smallest amount of precipitation. The spring precipitation also appeared to have a decreasing trend since 2000. We also find that spring precipitation of the South China has experienced a few abrupt changes: sudden increment at 1964, sudden decrement at 2002, and sudden increment at 1995. In addition to these abrupt changes, the precipitation could also be characterized by variability of multiple temporal scales, with dominant periodicities of 4 years, 8 years, and 14 years. The South China spring precipitation is also closely tied to the atmospheric circulations: when Aleutian Low strengthens, westerly weakens, and the center of the Western Pacific subtropical high shifts southeastward in the early spring; and the South China precipitation tends to be abundant (positive anomaly). In contrast, when Ural ridge strengthens, the southern branch of the East Asian trough weakens and the Western Pacific subtropical high shifts northwestward in the early spring, the South China precipitation tends to be reduced (negative anomaly).